Altered Default Mode Network Is Associated With Cognitive Impairment in CADASIL as Revealed by Multimodal Neuroimaging - Li, Panlong; Huang, Qi; Ban, Shiyu; Qiao, Yuan; Wu, Jing; Zhai, Yu; Du, Xiaoxia; Hua, Fengchun; Su, Jingjing (Frontiers in Neurology, 2021)
BACKGROUND AND PURPOSE: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) caused by mutations in NOTCH3 gene is a hereditary cerebral small vessel disease, manifesting with stroke, cognitive impairment and mood disturbances. Functional or structural changes in the default mode network (DMN), which plays important roles in cognitive and mental maintenance, have been found in a number of neurological and mental diseases. However, it is still unclear whether DMN is altered in CADASIL patients. METHODS: Multimodal imaging methods, including magnetic resonance imaging (MRI) and positron emission tomography (PET), were applied to evaluate the functional, structural and metabolic characteristics of DMN in 25 CADASIL patients and 42 healthy controls. RESULTS: Compared to controls, CADASIL patients had decreased nodal efficiency and degree centrality of the dorsal medial prefrontal cortex and hippocampal formation within DMN. Structural MRI and diffusion tensor imaging (DTI) showed decreased gray matter volume and fiber tracks presented in the bilateral hippocampal formation. Meanwhile, PET imaging showed decreased metabolism within the whole DMN in CADASIL. Furthermore, correlation analyses showed that these nodal characteristics, gray matter volume, and metabolic signals of DMN were related to cognitive scores in CADASIL. CONCLUSIONS: Our results suggested that altered network characteristics of DMN may play important roles in cognitive deficits of CADASIL.